The Tingkeban in Temanggung from an Anthropological Perspective - Baedhowi; Adib Subhan; Ouedraogo Saidou (Yayasan Azhar Amanaa Yogyakarta, 2024)
Tingkeban Ritual is one of the Javanese cultural traditions that continues to be preserved by communities in Temanggung Regency, particularly within the life-cycle rituals related to pregnancy. This tradition functions not merely as a ceremonial practice, but also embodies philosophical, religious, and social values that reflect the Javanese worldview. This study aims to analyze the meanings and functions of the Tingkeban Ritual from an anthropological perspective, with a focus on ritual symbolism and its relevance to the social and religious life of the community. This research employs a qualitative approach with a descriptive-interpretative method. Data were collected through participant observation, in-depth interviews with traditional leaders, religious figures, and community members involved in the ritual, as well as documentation studies. The data were analyzed qualitatively using a symbolic interpretive approach to uncover the philosophical meanings embedded in ritual elements such as rujak, nasi tumpeng, and ayam ingkung, and their relationship to religious values and social concern. The findings indicate that the Tingkeban Ritual contains philosophical values emphasizing hope for safety, balance, and blessing, while simultaneously strengthening social relations and community solidarity. This tradition also represents a dialectical process between local Javanese culture and Islamic religious values, functioning as a medium for cultural and spiritual education within the community. Thus, the Tingkeban Ritual serves not only as a form of cultural heritage but also plays a significant role in maintaining identity, social harmony, and the sustainability of Javanese cultural values in Temanggung.